Annulotrema (Monogenea: Dactylogyridae) from Hydrocynus brevis (Characiformes: Alestidae) in Senegal, with descriptions of two new species and remarks on Annulotrema pikei - Řehulková, Eva; Musilová, Naďa; Gelnar, Milan (Parasitology research, 2014)
Two new species of Annulotrema Paperna & Thurston, 1969 were collected from the gills of the African tiger fish, Hydrocynus brevis, from the Gambia River basin in the Niokolo-Koba National Park, Senegal. Annulotrema besalis n. sp. is characterized by having a male copulatory organ (MCO) composed of an arcuate copulatory tube articulated to an eight-shaped accessory piece with terminal claw. The new species resembles Annulotrema pikei (Price, Peebles & Bamford, 1969) in having morphologically similar types of haptoral sclerites and MCO. As a result of the differential diagnosis made for A. besalis n. sp., new information on taxonomically important features of A. pikei is provided based on illustrations of the sclerotized parts of the holotype from Hydrocynus vittatus. The report of A. pikei on the gills of Hydrocynus forskahlii by Paperna in 1979 is shown to be erroneous. Annulotrema uncata n. sp. is similar to Annulotrema alestesimberi Paperna, 1973 in its possession of a coiled copulatory tube with about two and a half rings. Features distinguishing the new species include the sharply curved shaft of the ventral anchor, the base of the copulatory tube extending to a sock-like structure and a leech-shaped vagina. The necessity of emending the generic diagnosis of Annulotrema is briefly discussed.
Keywords: žábry; Senegal; Animals; Characiformes; mužské pohlaví; Fish Diseases; ženské pohlaví; zvířata; Trematode Infections; Female; nemoci ryb; Gills; řeky; Male; Rivers; infekce červy třídy Trematoda; Trematoda